Accounting Computer Systems as a Part of the Information System in the Textile Company - Stepien, M. (Электронное моделирование, 2008)
Economic information becomes the indispensable tool for decision-making in a market economy. The preparation, processing and delivery of the information to the decision-making individuals provides the competitive advantage on the market. Accounting computer systems, which constantly observe, register and process the economic operations of the company, may provide the reliable information for the management of the economic unit.